2015
DOI: 10.3758/s13414-015-0923-4
|View full text |Cite
|
Sign up to set email alerts
|

Mask-triggered thrust reversal in the negative compatibility effect

Abstract: Rapid motor responses to visual stimuli can involve both the activation and inhibition of motor responses. Here, we trace the early processing dynamics of response generation, examining whether activation and inhibition events form a strict sequence when elicited by sequential stimuli, as we would expect if motor events are driven by fast, stimulustriggered feedforward sweeps. We employed identical stimuli in two complementary paradigms. In response priming, responses to a target stimulus are speeded or slowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 79 publications
(116 reference statements)
1
9
0
Order By: Relevance
“…(2008) and Eimer and Schlaghecken (1998) . Crucially, the NCE appears ∼360 ms after mask onset in every condition, an estimate very similar to the 350 ms estimate obtained by looking at pointing movement trajectories ( Schmidt et al., 2015 ).…”
Section: Obtaining Descriptive Statistics For Discrete Time Units: the Life Tablesupporting
confidence: 80%
See 1 more Smart Citation
“…(2008) and Eimer and Schlaghecken (1998) . Crucially, the NCE appears ∼360 ms after mask onset in every condition, an estimate very similar to the 350 ms estimate obtained by looking at pointing movement trajectories ( Schmidt et al., 2015 ).…”
Section: Obtaining Descriptive Statistics For Discrete Time Units: the Life Tablesupporting
confidence: 80%
“…If such an early response is emitted, it is always correct for congruent primes and always incorrect for incongruent primes, as shown by the ca (t) functions. This clearly indicates that these initial responses are triggered exclusively by the prime without any contribution from the target (the crucial prediction of the rapid-chase theory of response priming; Schmidt et al., 2006 , 2011 , 2015 ).…”
Section: Obtaining Descriptive Statistics For Discrete Time Units: the Life Tablementioning
confidence: 87%
“…However, it is unclear if active response inhibition was playing a role in the generation of the behavior in Experiment 2 . Panis and Schmidt ( 2016 ) and Schmidt, Hauch, and Schmidt ( 2015 ) showed that a second stimulus can trigger active and selective inhibition of the response triggered by a first stimulus, within about 360 ms. For example, for SOA combinations 133/133 and 187/80 we see that CI has a lower conditional accuracy than II for bins after 225 ms. This might be caused by active inhibition of the first compatible response, creating an even stronger activation of the incompatible response channel in condition CI than in II.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the NCE is generally perceived as a behavioural indicator of the occurrence of unconscious inhibitory processes; that is, the prime automatically triggers an initial activation of their corresponding motor response, which is subsequently inhibited. Within this framework, competing hypotheses assume either that the NCE reflects an automatic activation-followed-by-inhibition process (Bowman, Schlaghecken, & Eimer, 2006; Eimer, 1999; Eimer & Schlaghecken, 1998, 2002; Schlaghecken & Eimer, 2002, 2004) or that inhibition is triggered by perceiving the mask (Boy, Clarke, & Sumner, 2008; Jaśkowski, 2007, 2008; Jaśkowski, Białuńska, Tomanek, & Verleger, 2008; Schmidt, Hauch, & Schmidt, 2015). Schlaghecken and Eimer (2002) suggested that the perceptual strength of the prime must be sufficiently large to reach the inhibitory threshold, after which the inhibitory process can be triggered (inhibitory threshold account).…”
Section: Introductionmentioning
confidence: 99%